Post-Publication Gatekeeping: The Interplay of Publics, Platforms, Paraphernalia, and Practices in the Circulation of News. (June 2020) - Hermida, Alfred
The factors that shape the news that citizens are exposed to and act upon are a growing area of research. This article advances a framework to examine how issues and topics rise to prominence and gain attention following publication in a digital hybrid media ecosystem. The four elements (publics, platforms, paraphernalia, and practices) extend previous work by accounting for the actions of individuals in aggregate as publics, the impact of platforms as institutionalized spaces for news, the objects of media consumption and exposure, and the temporal and spatial contexts for practices of news circulation and consumption.